Effects of ketamine on hypoxic pulmonary vasoconstriction in the isolated perfused lungs of endotoxaemic mice - Busch, Cornelius; Spöhr, Fabian A.; Motsch, Johann; Gebhard, Martha-Maria; Martin, Eike; Weimann, Jörg (European journal of anaesthesiology, 2010)
Background and objective - During sepsis and endotoxaemia, hypoxic pulmonary vasoconstriction (HPV) is impaired. Sedation of septic patients in ICUs is performed with various anaesthetics, most of which have pulmonary dilatory properties. Ketamine is a sympathetic nervous system-activating anaesthetic that preserves cardiovascular stability. The effects of ketamine on the pulmonary vasculature and HPV during sepsis have not been characterized yet. - Methods - Therefore, isolated lungs of mice were perfused with ketamine (0, 0.1, 1.0, and 10 mg kg−1 body weight min−1) 18 h following intraperitoneal injection of lipopolysaccharide (LPS); untreated mouse groups served as controls (n = 7 per group, respectively). Pulmonary artery pressure (PAP) and pressure-flow curves during normoxic (FiO2 = 0.21) and hypoxic (FiO2 = 0.01) ventilation were obtained. - Results - HPV was reduced in endotoxaemic animals when compared with controls (means ± SD; ΔPAP control 103 ± 28% vs. LPS 23 ± 25%, P < 0.05). Ketamine caused a dose-dependent reduction of HPV in the lungs of control (ΔPAP 0 mg kg−1 min−1 ketamine 103 ± 28% vs. 10 mg kg−1 min−1 ketamine 28 ± 21%, P < 0.05) and septic animals (ΔPAP 0 mg kg−1 min−1 ketamine 23 ± 25% vs. 10 mg kg−1 min−1 ketamine 0 ± 4%, P < 0.05). Analysis of pressure-flow curves revealed that ketamine partly reversed the endotoxin-induced changes in basal pulmonary vascular wall properties rather than interfering with the HPV response itself. - Conclusion - Ketamine modified baseline pulmonary vascular properties, resulting in a reduced HPV responsiveness in untreated mice. Further, ketamine counteracted the LPS-induced changes in pulmonary vascular pressure-flow relationships, but did not affect impaired HPV in this murine endotoxaemia model.
Gesehen am 22.03.2023